2020
DOI: 10.1029/2020ja027939
|View full text |Cite
|
Sign up to set email alerts
|

Whole Atmosphere Model Simulations of Ultrafast Kelvin Wave Effects in the Ionosphere and Thermosphere

Abstract: This paper examines the response of the upper atmosphere to equatorial Kelvin waves with a period of ∼3 days, also known as ultrafast Kelvin waves (UFKWs). The whole atmosphere model Ground‐to‐topside model of Atmosphere and Ionosphere for Aeronomy (GAIA) is used to simulate the UFKW events in the late summer of 2010 and 2011 as well as in the boreal winter of 2012/2013. When the lower layers of the model below 30‐km altitude are constrained with meteorological data, GAIA is able to reproduce salient features … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 89 publications
2
13
0
Order By: Relevance
“…(2017). This serves as forcing from the lower atmosphere to the upper layers, thus enabling GAIA to reproduce the ionospheric response to meteorological forcing from below (e.g., Pancheva et al., 2012; Yamazaki, Miyoshi, et al., 2020). Simulations were performed for solar minimum conditions that were held constant using a solar activity index F 10.7 value of 68 solar flux unit (SFU; 10 −22 W m −2 Hz −1 ).…”
Section: Data Analysis Method and Modelmentioning
confidence: 99%
“…(2017). This serves as forcing from the lower atmosphere to the upper layers, thus enabling GAIA to reproduce the ionospheric response to meteorological forcing from below (e.g., Pancheva et al., 2012; Yamazaki, Miyoshi, et al., 2020). Simulations were performed for solar minimum conditions that were held constant using a solar activity index F 10.7 value of 68 solar flux unit (SFU; 10 −22 W m −2 Hz −1 ).…”
Section: Data Analysis Method and Modelmentioning
confidence: 99%
“…Modeling studies (e.g., Fang et al., 2009; Hagan et al., 2007; Jin et al., 2008, 2011) solidified our quantitative understanding of these observations. Analogous to A‐I coupling by tides, observational (Abdu et al., 2015; G. Liu et al., 2015; Onohara et al., 2013; Takahashi et al., 2007) and modeling (Chang et al., 2010; Gu et al., 2014; Yamazaki et al., 2020) studies demonstrated that quasi‐3‐days ultra‐fast Kelvin waves (UFKWs) also impart their variability on the ionosphere through the dynamo mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…Analogous to A-I coupling by tides, observational (Abdu et al, 2015;G. Liu et al, 2015;Onohara et al, 2013;Takahashi et al, 2007) and modeling (Chang et al, 2010;Gu et al, 2014;Yamazaki et al, 2020) studies demonstrated that quasi-3-days ultra-fast Kelvin waves (UFKWs) also impart their variability on the ionosphere through the dynamo mechanism.…”
mentioning
confidence: 99%
“…Studies of UFKW described their general characteristics (see Davis et al (2012) and references therein) and showed that UFKW can travel to thermospheric heights and also drive changes further up (Forbes 2000;Takahashi et al 2007;Forbes et al 2009;Chang et al 2010;Chen et al 2018); however, their effects on the IT region are yet to be examined in detail. Modelling studies are indicating significant effects of UFKW on MLT and IT region including day-to-day variability (Triplett et al 2019;Yamazaki et al 2020).…”
Section: Open Accessmentioning
confidence: 99%